The truth about securing your retirement with IRAs : the essential truths in 20 minutes - Wiesman, Steve (Truth about (FT Press), 2009)
All you need to know about every IRA, every 401(k) ... even HSAs, and more! · The truth about getting the most benefits at the lowest cost · The truth about avoiding the pitfalls that can kill your retirement · The truth about choosing the best strategies for you-- and your kids The Truth About Protecting Your IRAs and 401(k)s arms you with the up-to-the-minute knowledge you need to build your retirement income, as you reduce your costs, taxes, and risks! Consumer finance expert and nationally syndicated radio host Steve Weisman offers 48 quick, bite-size, just-the-facts information about every type of tax-advantaged retirement investments: self-directed, stretch, SIMPLE, SEP, Roth, and spousal IRAs, 401(k)s, and more. You'll find up-to-the-minute guidance on avoiding pitfalls that can cost you a fortune ... choosing the right retirement strategies for both you and your heirs ... planning retirement investments when you're a married or unmarried couple ... widening your 401(k) investment options ... and much more. Like every book in The Truth About Series, this book distills all the essential knowledge you need on a topic ... presents it clearly, simply, and quickly, with an "a-ha!" on every page ... and shows exactly how to put it to work in your daily life. Easy to read, easy to use, it's all you need to gain retirement security--and protect it for the rest of your life!